Value Driven Healthcare and Geriatric Medicine Implications for Today's Changing Health System - Powers, James S. (Springer International Publishing, 2018)
This book traces the origins of value-based purchasing and current geriatric care models to deliver value in the broader healthcare system. The text focuses on the three goals that are expected to remain at the center of healthcare: improving access to healthcare via insurance coverage, improving the patient's experience and quality of care, and effectively managing healthcare costs. Chapters cover the quality indicators of care, drivers for improved outcomes, and models of care as seen in geriatrics as they can be expanded upon for the larger system. The text also discusses some of the most critical periods for aging patients and the ways that these lessons can inform the larger system. These topics include transitioning from the hospital to the home setting, integrating care between geriatric workers, and staff training and the clinical pearls for all changing demographics. As the healthcare system evolves and the population ages, Value Driven Health Care proves to be a vital resource for geriatricians, primary care physicians, specialists who work with aging patients, hospital administrators, healthcare educators, healthcare organizations, and all medical professionals working with aging patients and patients affected by healthcare reform.